Role of Reduced Sarco-Endoplasmic Reticulum Ca2+-ATPase Function on Sarcoplasmic Reticulum Ca2+ Alternans in the Intact Rabbit Heart - Wang, Lianguo; Myles, Rachel C.; Lee, I-Ju; Bers, Donald M.; Ripplinger, Crystal M. (Frontiers in Physiology, 2021)
Sarcoplasmic reticulum (SR) Ca2+ cycling is tightly regulated by ryanodine receptor (RyR) Ca2+ release and sarco-endoplasmic reticulum Ca-ATPase (SERCA) Ca2+ uptake during each excitation-contraction coupling cycle. We previously showed that RyR refractoriness plays a key role in the onset of SR Ca2+ alternans in the intact rabbit heart, which contributes to arrhythmogenic action potential duration (APD) alternans. Recent studies have also implicated impaired SERCA function, a key feature of heart failure, in cardiac alternans and arrhythmias. However, the relationship between reduced SERCA function, and SR Ca2+ alternans is not well understood. Simultaneous optical mapping of transmembrane potential (Vm) and SR Ca2+ was performed in isolated rabbit hearts (n=10) using the voltage-sensitive dye RH237, and the low-affinity Ca2+ indicator Fluo-5N-AM. Alternans was induced by rapid ventricular pacing. SERCA was inhibited with cyclopiazonic acid (CPA; 1-10µM). SERCA inhibition (1, 5, and 10µM CPA), resulted in dose-dependent slowing of SR Ca2+ reuptake, with the time constant (tau) increasing from 70.8±3.5ms at baseline to 85.5±6.6ms, 129.9±20.7ms, and 271.3±37.6ms, respectively (p<0.05 vs. baseline for all doses). At fast pacing frequencies, CPA significantly increased the magnitude of SR Ca2+ and APD alternans, most strongly at 10 µM (pacing cycle length=220ms: SR Ca2+ alternans magnitude: 57.1±4.7 vs. 13.4±8.9 AU; APD alternans magnitude 3.8±1.9 vs. 0.2±0.19 AU; p<0.05 10 µM CPA vs. baseline for both). SERCA inhibition also promoted the emergence of spatially discordant alternans. Notably, at all CPA doses, alternation of SR Ca2+ release occurred prior to alternation of diastolic SR Ca2+ load as pacing frequency increased. Simultaneous optical mapping of SR Ca2+ and Vm in the intact rabbit heart revealed that SERCA inhibition exacerbates pacing-induced SR Ca2+ and APD alternans magnitude, particularly at fast pacing frequencies. Importantly, SR Ca2+ release alternans always occurred before the onset of SR Ca2+ load alternans. These findings suggest that even in settings of diminished SERCA function, relative refractoriness of RyR Ca2+ release governs the onset of intracellular Ca2+ alternans.